2010
DOI: 10.1007/s10344-010-0402-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the distribution of short-toed eagle (Circaetus gallicus) in semi-arid Mediterranean landscapes: identifying important explanatory variables and their implications for its conservation

Abstract: Mediterranean semi-arid landscapes are currently experiencing accelerated land use changes which are affecting species distributions. An important fraction of the European short-toed eagle (Circaetus gallicus) population, a specialised snake predator, breeds in this kind of landscapes. Information on the habitat characteristics that may affect the occurrence of this species is of paramount importance to try to evaluate how this species could be affected by ongoing territory changes. In this study, we use hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
(44 reference statements)
2
20
1
3
Order By: Relevance
“…Forests are important for short-toed snake eagles because the species nests in these habitats; this is in agreement with previous research (Sa´nchez-Zapata and Calvo 1999; Bustamante and Seoane 2004;Bakaloudis et al 2005;Lo´pez-Iborra et al 2011). As shown by the high Wald value of the variable ''square root forest'' (Table 2), the increase of forested areas is important for the presence of short-toed snake eagles; however, there is a threshold value beyond which the extension of forests becomes limiting for this species, since snake eagles hunt in open areas where reptilian prey are probably abundant and most accessible (see Moreno-Rueda and Pizarro 2007;Bakaloudis 2009;Lo´pez-Iborra et al 2011). Mean altitude may be important in the BRT model because, in Italy, forests are almost absent from lowlands, such as the Po valley, and because agriculture on the Italian plains is intensive (monoculture).…”
Section: Ecological Parameterssupporting
confidence: 88%
See 1 more Smart Citation
“…Forests are important for short-toed snake eagles because the species nests in these habitats; this is in agreement with previous research (Sa´nchez-Zapata and Calvo 1999; Bustamante and Seoane 2004;Bakaloudis et al 2005;Lo´pez-Iborra et al 2011). As shown by the high Wald value of the variable ''square root forest'' (Table 2), the increase of forested areas is important for the presence of short-toed snake eagles; however, there is a threshold value beyond which the extension of forests becomes limiting for this species, since snake eagles hunt in open areas where reptilian prey are probably abundant and most accessible (see Moreno-Rueda and Pizarro 2007;Bakaloudis 2009;Lo´pez-Iborra et al 2011). Mean altitude may be important in the BRT model because, in Italy, forests are almost absent from lowlands, such as the Po valley, and because agriculture on the Italian plains is intensive (monoculture).…”
Section: Ecological Parameterssupporting
confidence: 88%
“…Its effect is the opposite of that documented in Spain (Lo´pez-Iborra et al 2011), where latitudinal increase was shown to have a negative effect on the distribution of the species. By contrast, we found that eagle presence seems to increase with latitude.…”
Section: Ecological Parameterscontrasting
confidence: 69%
“…VIF values > 10 (López‐Iborra et al . ) indicate collinearity between variables. We also calculated the proportion of process variance explained by the covariates: R 2 _var = (σ 2 (t) – σ 2 (cov) )/σ 2 (t) , where σ 2 (t) and σ 2 (cov) are the estimates of process variance in the random effects model without and with the covariate, respectively (Altwegg et al .…”
Section: Methodsmentioning
confidence: 99%
“…dispersal or competition), as well as historical and contingent factors that shape species distributions; aiming at the selection of the "best" model for each species in terms of predictive accuracy (e.g. Pearce et al 2001, Cabeza et al 2004, Claridge et al 2008, López-Iborra et al 2011. Studies modelling the habitat preference of species commonly follow a correlative approach based on multiple regression methods (e.g.…”
Section: Introductionmentioning
confidence: 99%